Legal Protection For Consumers For Non-Conformity In The Quality Of Goods Purchased On The Tiktok Shop Application - Asman Siagian; Rahmadany; Siti Nurhayati; Lidya Rahmadani Hasibuan (Yayasan Multidimensi Kreatif, 2025)
The development of information and communication technology has encouraged the emergence of various electronic commerce platforms (e-commerce), one of which is TikTok Shop. The ease of online shopping carries its own legal consequences, especially when there is a discrepancy between the quality of the goods advertised and the goods received by consumers. This study aims to analyze the form of legal protection provided to consumers for the inconsistency in the quality of goods purchased through the TikTok Shop application, as well as legal remedies that consumers can take in order to fight for their rights. The research method used is normative legal research with a statutory approach and a conceptual approach. Data sources include primary legal materials such as Law Number 8 of 1999 concerning Consumer Protection, Law Number 11 of 2008 jo. Law Number 19 of 2016 concerning Electronic Information and Transactions, Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, and Regulation of the Minister of Trade Number 31 of 2023 concerning Business Licensing, Advertising, Coaching, and Supervision of Business Actors in Trade through Electronic Systems. The results of the study show that consumers who experience a discrepancy in the quality of goods are entitled to legal protection both preventively and repressively. Preventively, the state has provided regulations that require business actors to provide true, clear, and honest information. Repressively, consumers can take the dispute resolution route through the Consumer Dispute Resolution Agency (BPSK), district courts, or the settlement mechanism provided by the TikTok Shop platform itself. This study recommends strengthening government supervision of electronic commerce and improving consumer digital literacy.